Pengaruh Komposisi Media dan Dosis Teh Kompos Daun Gamal terhadap Pertumbuhan dan Hasil pada Tanaman Sawi Hijau (Brassica juncea L.) Dalam Budidaya Sistem Irigasi Genangan Terbatas - Yuliana Boe (Savana Cendana, 2022)
The research aimed to determine the effect of planting media composition and dose of gamal leaf compost tea, as well as to obtain the most optimal composition of planting media and dosage of compost tea to increase the growth and yield of mustard (Brassica junceaL.) in irrigation inundation systems. November 2019 in the experimental garden of the Faculty of Agriculture, University of Timor using a 3x3 factorial Completely Randomized Design (CRD) repeated 3 times. The first factor is the composition of the growing media, namely: 70% sand: 15% compost: 15% charcoal, 70% sand: 20% compost: 10% charcoal, 70% sand: 25% compost: 5% charcoal. The second factor is: compost tea dose, namely: 15%, 20% and 25%. The results showed that the composition of the growing media and the dose of compost tea did not interact on all the observed parameters. The main effect of giving the composition of planting media sand:compost:husk charcoal (70:25:5) was significantly different in providing better growth and yield of mustard greens, due to the increased concentration of compost in the medium. The main effect of giving a dose of 25% compost tea gave better growth and yields but not significantly different.